O caranguejo e a construção da Identidade Cultural de Aracaju: uma análise folkcomunicacional - Santana, Flávio Menezes (2020)
Aracaju, capital of Sergipe, is traditionally known for its historical relationship with the mangrove ecosystem and the crab has become one of the main constituent elements of its identity. As we consider that identities are built in accordance with the structure and hierarchy of society, we understand communication as a mechanism for the dissemination of cultural standards that constantly organizes and articulates social relations. Thus, from a folkcommunicational perspective, this research seeks to analyze a community of crab scavengers and the identity addressed in the aracajuano media space, facing the process of forming the capital's cultural identity. For this, semi-structured interviews were analyzed with waste pickers and crab pickers from the community of Povoado Coqueiro, in São Cristóvão / SE; and news articles from newspapers and news portals in the capital of Sergipe, published during the months of August 2015 and 2016, the period of the Crab Festival. This investigation reveals that the crab has a strong historical relationship with the capital of Sergipe...